Time variability analysis for damage detection in flexible pavement using infrared thermography - Pacara Copa, Marina; Aquino Rocha, Joaquin Humberto; Ledezma Perez, Jahel Sarvia (Revista ALCONPAT, 2020)
This document discusses the time range to optimize and understand infrared thermography results when used on damage detection for flexible pavement. A monitoring activity was performed during 14 continuous hours (5:00 a.m. to 7:00 p.m.) for four study areas in a centrally located avenue in Cochabamba City, Bolivia. This activity evidenced an effective time range to take thermographic images from 11:00 a.m. to 4:00 p.m. Damage visualization by differential colorimetry in thermograms at different times was also verified. This test enables locating areas where a detailed inspection may be performed. As a limitation, its sensibility to changes under environmental conditions is evident.